EXPLORING THE RELATIONSHIP BETWEEN KING'S CHARACTERISTICS AND EMOTIONAL WELL-BEING IN ARMENIAN FAIRY TALES - Asriyan, Elina (Modern Psychology, 2024)
Our research shows that fairy tales can be considered as a source of formation of primary social beliefs formed in society about objects, people, relationships, trust, well-being and other phenomena. The purpose of this article is to investigate and study the description of the king's (as a leader) characteristics in the Armenian fairy tales, as well as to investigate the coefficient of emotional wellbeing of the fairy tales. Research data suggests that there is a connection between a leader's positive image and emotional well-being.
Keywords: fairy tale; wellbeing; emotion; king; image; leader